Islamism and Jihad: The Problem With Western Taxonomies - Mohamed, Mohamed Mosaad Abdelaziz (Universitas Islam Negeri Mataram, 2023)
Explaining the confusing classification of 'political Islam' as Islamism/Jihad, I argue that this classification is epistemologically grounded in 1) Christian morality, 2) political secularism, and 3) modern ideologism. I contrast this epistemology to an Islamic-friendly epistemology, framed by a specific theory of meaning, a priority of historical cases over abstract principles in determining the correct action, and a priority of the apparent action in deciding its rule legally over any internal intention or implied subjectivity. Following this discussion, I propose and introduce four legal concepts that traditionally articulate Muslims’ political protest: 1) jihad, 2) khurūj, 3) qitāl al-fitnah, and 4) naṣīḥah. Contrasting this legal classification against the conventional Islamism/Jihad classification, I explain the advantages of using Islamic-friendly concepts to understand and frame Muslims’ political protest. I also explain that these four concepts are essentially neither good nor evil, neither true nor false. They are rooted neither in ideology nor in morality. They are legal concepts where each one of them can be ruled, depending on a specific historical situation, as wājib, mustaḥab, mubāḥ, makrūh, or ḥarām.